The Development Of Correctional System Of Narcotic And Prohibited Drugs Using The Criminon Program At Cipinang Narcotics Special Penitentiary - Raidin, Raidin; Raihan, Raihan (International Journal of Educational Research & Social Sciences, 2023)
Broadly speaking, coaching at the Narcotics Special Penitentiary has the same goal, namely to rehabilitate convicts so that they become good and law-abiding citizens. However, in the implementation of coaching, there are still obstacles that cause the coaching program to not run effectively. This research is aimed at answering questions related to the implementation of fostering narcotics case convicts at the Narcotics Special Penitentiary and what are the obstacles encountered in the implementation of coaching for narcotics case convicts. This is a research that uses the library research method but the data collection is also complemented by semistructured interviews with drug case convicts, coaching program instructors and also officials responsible for coaching program licenses. The results of the study indicate that the implementation of the program for fostering convicts of narcotics cases using the Criminon method cannot be said to be effective. This can be seen from a number of obstacles encountered during program implementation. These obstacles are not only in the program, but also in the inmates who are coached and the instructors who do not understand the theories of the Criminon program.